Construction of a multi-regional input-output table for Nagoya metropolitan area, Japan - Mitsuo Yamada (Journal of Economic Structures, 2015)
Japan has many input-output tables, national and regional. We focus on the Nagoya metropolitan area, in which Toyota Motors is headquartered along with many industries manufacturing transport equipment, machine tools and other machinery. This area is included in the region covered by three prefectures; Aichi, Gifu, and Mie. To construct a multi-regional input-output table from these prefectures, we first break down each prefecture table with 186 sectors into several smaller sub-regional tables. Then we combine each table into one multi-regional input output table, consisting of 14 sub-regions. Transaction values among sub-regions of each sector are estimated by the gravity-RAS method, in which the initial values are obtained by the gravity model. Using the multi-regional table, we discuss the structural characteristics of the Nagoya metropolitan area. We then show a way to cope with the various inconsistencies of regional definitions, administrative and economic, in the input-output analysis.
Keywords: R15; R12; 330; Multi-regional input-output table; Gravity-RAS method; Average Propagation Lengths; Nagoya metropolitan area; Crosshauling